2010
DOI: 10.1007/s13213-009-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an inducible, chromosomally encoded benzo [a] pyrene (BaP) degradation pathway in Bacillus subtilis BMT4i (MTCC 9447)

Abstract: Benzo [a] pyrene (BaP), a pentacyclic polyaromatic hydrocarbon, is 1 of the 12 target compounds defined in the new US Environmental Protection Agency strategy for controlling persistent, bioaccumulative, and toxic pollutants. We previously isolated a novel strain Bacillus subtilis BMT4i capable of utilizing BaP as sole source of carbon and energy. The present study investigated (1) whether the BaP degradation pathway is inducible, and (2) whether it is plasmid-encoded. Furthermore, physical (temperature, pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Furthermore, the bacterial isolates which possessed plasmid and after total curing of their plasmid showed no change in PAHs degradability suggested that their PAHs degradability could be chromosomally mediated as earlier reported (Lily et al, 2010). In addition, the observed altered growth on PAHs by acridine orange treated isolates indicated that the presence of chemicals may possibly induce the translocation or recombination of some gene(s) in the bacteria.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, the bacterial isolates which possessed plasmid and after total curing of their plasmid showed no change in PAHs degradability suggested that their PAHs degradability could be chromosomally mediated as earlier reported (Lily et al, 2010). In addition, the observed altered growth on PAHs by acridine orange treated isolates indicated that the presence of chemicals may possibly induce the translocation or recombination of some gene(s) in the bacteria.…”
Section: Discussionsupporting
confidence: 68%
“…Bacillus subtilis strain: The Bacillus subtilis BMT4i (MTCC 9447), isolated from automobile contaminated soil is an efficient degrader of HMW-PAHs including BaP, a potent carcinogen [16][17][18] was used in this study. The culture was maintained on nutrient agar slants at 4 o C.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the above, the present study reports the production, partial purification, and characterization of α-amylase from a novel benzo-a-pyrene (BaP) degrading Bacillus subtilis BMT4i (MTCC 9447) previously isolated from automobile contaminated soil that is capable of degrading high molecular weight polycyclic aromatic hydrocarbons (HMW-PAHs) including BaP [16][17][18]. Production conditions were also optimized (time, pH, carbon source, nitrogen source and CaCl 2 concentration) to achieve high enzyme production and better enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited information is available on BaP degradation pathway in genus Bacillus despite of its species being shown as potent BaP degraders [19,22,23]. A bacterial consortium of Bacillus cereus and Bacillus vireti isolated from petrochemical soil has been reported to degrade BaP into cis-4-(8-hydroxy-pyren-7-yl)-2-oxobut-3-enoic acid, a ring cleavage product of 9,10-dihydrodiol [23].…”
Section: Introductionmentioning
confidence: 99%
“…A bacterial consortium of Bacillus cereus and Bacillus vireti isolated from petrochemical soil has been reported to degrade BaP into cis-4-(8-hydroxy-pyren-7-yl)-2-oxobut-3-enoic acid, a ring cleavage product of 9,10-dihydrodiol [23]. We have shown previously that B. subtilis BMT4i (MTCC 9447) degrades BaP very efficiently up to 84.66% in 28 days via chromosomally encoded pathway [19,22].…”
Section: Introductionmentioning
confidence: 99%